Parole Revoked: Justifying Rerelease for Juvenile Lifers - Kokkalera, Stuti S. (Criminal justice and behavior, 2022)
A juvenile lifer’s parole can be revoked and justified for technical or new crime violations of supervision conditions. We analyze narratives contained in revocation decisions issued to juvenile lifer candidates by one state parole board. Our qualitative content analysis reveals that most parole revocations stem from technical violations rather than any new criminal activity. In addition, decision statements qualify aspects of a juvenile lifer candidate’s case in opposite ways, where identified themes are presented as accomplishments to grant parole, but as claims made by the candidate to deny rerelease. In categorizing candidates as deserving or undeserving of parole, suitability for rerelease is represented in the parole board’s interpretation of risk in terms of a candidate’s moral responsibility. By doing so, parole revocation review decisions avoid acknowledging the obstacles in juvenile lifer reentry.